The disappeared: the hidden victims of Northern Ireland's conflict - Peake, Sandra (Palgrave studies in compromise after conflict, 2024)
This short book focuses on the Disappearances that occurred during the Troubles in Northern Ireland. Using in-depth interviews with thirteen families of those individuals who were abducted, murdered and secretly buried from the 1970's onwards, this book examines the experience of the families and communities left behind. Through an exploration of the historic and cultural origins of the contemporary IRA and how they came to be in the position of power within Catholic/Nationalist communities during the troubles, the context to the disappearances are presented. This book reviews the journey undertaken by the families, from the initial disappearance of their loved one and the suffocating silence that followed, through their coming together as a self-help group. It follows their lobbying on a national and international basis leading to the return of the bodies of some of their loved ones and the solidarity which leads them to fight on as a group to recover the bodies that remain missing. It also examines the involvement of the British and Irish and American governments in the set up of the International Commission for the Location of Victim's Remains and tells the story of the Clinton's personal involvement in supporting the families in their ongoing quest for recovery. It is written accessibly for researchers and practitioners. Sandra Peake is Honorary Professor of Practice at Queen's University Belfast. She was awarded her PhD at University College Cork in 2022. She is a nurse by background. In 1995, Sandra was appointed CEO of WAVE Trauma Centre, a small voluntary group established in 1991, and was the organisation's first paid employee. Orla Lynch is currently Dean and Senior Lecturer in Criminology at University College Cork, Ireland. She has a PhD in Applied Psychology. Orla has written extensively on victims and victimhood, as well as on the psychology of political violence. Orla is a Senior Fellow with Hedayah and Resolve (United States Institute of Peace) and is a member of the committee of Experts on Hate Crime at the Council of Europe